Design and Simulation Studies of W-Band Gyro-Twystron Using Clustered Cavities - Yadav S.G.; Veera Babu V.; Thottappan M. (My University, 2025)
The present work explores the study of clustered cavity concept to broaden the bandwidth of W-band gyro-twystron at the cost of minimal reduction in gain. By revisiting the analytical theory developed for cavity-based gyro-amplifiers, a multicavity gyro-twystron operating in TE01 mode at 94 GHz with clustered cavity has been studied. The optimization is aimed at effectively expanding the bandwidth with a minimal cost of amplifier gain. The analytical observations are validated through 3-D particle-in-cell (PIC) simulations. The PIC simulation predicted an radio frequency (RF) output power of ~82 kW for an RF input of 20 W with the dc values of 65 kV and 6 A with a 4% velocity spread, which led to an electronic efficiency of ~20% and a gain of ~36 dB. The half power bandwidth that has been achieved with the use of clustered cavity is ~3 GHz, which is twice that of the bandwidth obtained in the stagger-tuned cavities. This enhancement in half-power bandwidth, along with the improved normalized gain bandwidth product and minimal loss in gain, positions the clustered cavity gyro-twystron as an efficient source for various radar applications. © 1973-2012 IEEE.